Development of coconut water-pineapple juice blend in doy packs - De Castro, Ma. Lourdes F.; Villarino, Blanca J. (Quezon City College of Home Economics, University of thePhilippines, 2009)
ABSTRACT The study aimed to develop an aseptically pasteurized coconut water-pineapple juice blend packed in DOY pouches. Proportions of coconut water from mature fruits and pineapple juice that produced mixtures (adjusted with constant TSS) with pH levels less than or equal to 4.0 were investigated. The most appropriate pasteurization treatment (90oC, 80oC, and 70oC for 15 sec) was then determined through physicochemical and sensory analyses. Lastly, product quality changes during storage at ambient and refrigerated temperatures were monitored. Among the tested coconut water and pineapple juice proportions, three formulations namely: 4:1, 3:1, and 2:1 were chosen, with the 4:1 ratio rated the most acceptable. Additionally, treatment of 70oC for 15 sec was found to be the most acceptable by consumers. Storage of the aseptically processed and packed formulation showed that freezing of the products rendered it more stable compared to the ambient storage. The results confirmed that coconut water from mature fruits and pineapple juice may produce a blend which may be aseptically pasteurized and packed, with desirable characteristics that may be retained for a longer period when stored at low temperatures.
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Fruit juices